Technological Aspect in the Concept of Advanced Development - G. H. Batov; Z. H. Kumisheva; A. B. Tlisov (Модернизация, инновация, развитие, 2019)
Purpose: in the Arsenal of economic theory, there are many models applicable to the development of the country's economy. Currently, along with the need for the development of the digital economy, various paradigms are proposed, including advanced development. The purpose of the study is to show that advanced development is a multidimensional phenomenon, it includes many factors, including technology. The task is to reveal the role of technology in the advanced development of the region.Methods: the methodological basis of the study is based on the use of a systematic approach and General scientific methods: scientific abstraction, analysis and synthesis, generalization, system-structural analysis, methods of statistical analysis and groupings.Results: it is proved that in the conditions of increased competition between the countries the most acceptable is the transition to the paradigm of advanced development. The structure of the model of advanced development includes various factors, one of which is the technology with the capabilities that allow you to become important drivers of development. The adoption of the proposed approach will ensure sustainable technological development and increase the level of independence from external factors.Conclusions and Relevance: in order to manage emerging new technologies a new way of thinking and behavior is needed, they must be supported by appropriate institutions. This conclusion is due to the fact that the development of new technologies is subject to a certain rule, which is mandatory. The implementation of advanced development becomes possible in the event that economic entities will be able to fully master all the functionality of new technologies.